COUNSELLING STRATEGIES FOR REDUCING DEPRESSION AND SUICIDAL IDEATION AMONG STUDENTS OF TERTIARY INSTITUTIONS IN NIGERIA - Rasaq Abimbola FADIPE; Falilat Anike OKESINA (Annals of the University of Craiova for Journalism, Communication and Management)
Students undergo a significant transitional phase from adolescence to adulthood, which is widely recognized as one of the most challenging periods in an individual's life. These students grapple with various issues such as adapting to school life, impulsive behaviour, feelings of isolation, cultural identity, academic performance, homesickness, financial difficulties, and depression, among other concerns. The paper therefore highlights the concept and types of depression, concept and types of suicidal ideation, symptoms of depression and suicidal ideation, risk factors for depression and suicidal ideation, effects of depression and suicidal ideation, and counselling strategies for reducing depression and suicidal ideation. Based on the review, it was suggested that students in school should seek guidance and counselling when experiencing depression so that early intervention would prevent the problem of suicidal ideation from escalating. Counsellors and other professional personnel should become aware of the potential factors that can lead to depression and suicidal ideation in order to provide adequate counselling to students where necessary on campus.